2017
DOI: 10.1002/cbdv.201700294
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of New Natural Phenolic (2E,4E,6E)‐Octa‐2,4,6‐trienoic Esters

Abstract: In the present study the esterification of the OH groups of resveratrol, caffeic acid, ferulic acid, and β-sitosterol with an antioxidant polyconjugated fatty acid, (2E,4E,6E)-octa-2,4,6-trienoic acid, was achieved. As the selective esterification of OH groups of natural compounds can affect their biological activity, a selective esterification of resveratrol and caffeic acid was performed by an enzymatic approach. The new resulting compounds were characterized spectroscopically (FT-IR, NMR mono, and bidimensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…In particular, of the compounds identified, n‐hexadecanoic acid (palmitic acid) and β‐sitosterol have been reported to promote the migratory and/or proliferative activities in monocytes, neural stem cells, fibroblasts, and endothelial cells [27–30] . In addition, n‐hexadecanoic acid and β‐sitosterol have been reported to promote keratinocyte proliferation, [31,32] which suggests these two compounds contributed to SCF absolute‐induced HaCaT cell proliferation. To the best of our knowledge, the present study provides first evidence that SCF absolute promotes the migration and proliferation of keratinocytes.…”
Section: Discussionmentioning
confidence: 95%
“…In particular, of the compounds identified, n‐hexadecanoic acid (palmitic acid) and β‐sitosterol have been reported to promote the migratory and/or proliferative activities in monocytes, neural stem cells, fibroblasts, and endothelial cells [27–30] . In addition, n‐hexadecanoic acid and β‐sitosterol have been reported to promote keratinocyte proliferation, [31,32] which suggests these two compounds contributed to SCF absolute‐induced HaCaT cell proliferation. To the best of our knowledge, the present study provides first evidence that SCF absolute promotes the migration and proliferation of keratinocytes.…”
Section: Discussionmentioning
confidence: 95%
“…Exposure to the new resveratrol derivative resulted in a significant increase in keratinocyte proliferation after 72 h of incubation, and the authors concluded that esterification also leads to an improvement in cell proliferation. The results obtained by Gandolfi et al (2017) encourage the use of this molecule as an antioxidant and/or anti‐inflammatory agent in dermocosmetic applications. Our results reflect the similar protective effects in ovarian cells.…”
Section: Discussionmentioning
confidence: 86%
“…FEHH4‐1 showed enhanced antiproliferative and pro‐apoptotic activities against Jurkat leukemia CD4 + T‐cells compared to RSV, with no results in normal cells. Gandolfi et al (2017) investigated the proliferative activity of newly synthetized resveratrol triester (esterification of ‐OH groups with an antioxidant polyconjugated fatty acid, [2 E ,4 E ,6 E ]‐octa‐2,4,6‐trienoic acid) on normal human keratinocyte NCTC 2544 cells. Exposure to the new resveratrol derivative resulted in a significant increase in keratinocyte proliferation after 72 h of incubation, and the authors concluded that esterification also leads to an improvement in cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, GC/MS analysis identified 12 compounds in LMFAb. In particular, β-sitosterol has been reported to promote keratinocyte proliferation [ 36 ], implying a potential contribution of β-sitosterol to LMFAb-promoted HaCaT cell proliferation. Therefore, LMFAb may facilitate re-epithelization of the skin by promoting keratinocyte migration and proliferation.…”
Section: Discussionmentioning
confidence: 99%